2022
DOI: 10.3390/ma15020612
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization of Granulated Sulfur Fertilizers and Their Effects on a Sandy Soils

Abstract: There is a potential for using sulfur waste in agriculture. The main objective of this study was to design a granular fertilizer based on waste elemental sulfur. Humic acids and halloysite were used to improve the properties and their influence on soil properties. This is the first report on the use of proposed materials for fertilizer production. The following granular fertilizers were prepared (the percentage share of component weight is given in brackets): fertilizer A (waste sulfur (95%) + halloysite (5%))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…of soil, found that this treatment had slightly affected the soil pH (during a 120-day incubation experiment). Similar results were presented by Lisowska et al [36], after the introduction of 20 mg S 0 /kg d.m. of soil and soil incubation for 90 days.…”
Section: Value Of Soil Ph Kclsupporting
confidence: 90%
“…of soil, found that this treatment had slightly affected the soil pH (during a 120-day incubation experiment). Similar results were presented by Lisowska et al [36], after the introduction of 20 mg S 0 /kg d.m. of soil and soil incubation for 90 days.…”
Section: Value Of Soil Ph Kclsupporting
confidence: 90%
“…Its use for fertilization purposes would be associated with the risk of environmental pollution and excessive accumulation of trace elements in food products. The use of waste materials as a means of food production is always associated with risk for the quality of the product [ 71 , 72 , 73 , 74 ]. Therefore, waste quality should be controlled regularly, with a frequency consistent with the previously conducted risk analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While halloysite mineral itself does not present any threat to the environment, its existence in soil can have an impact on the chemical equilibrium. Halloysite can increase the pH of the soil, making it more alkaline [66,67]. His alteration in pH can be disadvantageous for certain plant species, particularly those that thrive in acidic conditions.…”
Section: Discussionmentioning
confidence: 99%